Immunohistochemical analysis of sensory corpuscles in human transplants of the anterior cruciate ligament - D. Rebmann (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background Sensory nerve endings in ligaments play an important role for the proprioceptive function. Clinical trials show that the sense of body position does not fully recover in the knee joint after reconstructive surgery of the ruptured anterior cruciate ligament. The aim of this study is to identify sensory corpuscles in autogenous and allogenous transplants of the ligament and to compare their quantity between the used allografts and autografts. Methods Thirty-three patients were included in this study. Three patellar tendon allografts, 14 patellar tendon autografts and 12 semitendinosus autografts were harvested during revision surgery after traumatic rerupture of the graft. The control consisted of 4 healthy anterior cruciate ligaments after fresh rupture. After haematoxylin staining, immunohistochemical analysis was performed using antibodies against S100, p75 and PGP9.5. Microscopical examination was carried out, and the number of mechanoreceptors was counted. Statistical analysis was performed using the Mann-Whitney U test. Results Two types of mechanoreceptors were identified in each graft: Ruffini corpuscles and free nerve endings. The number of Ruffini corpuscles per square centimeter was the highest in the control. Comparing the grafts, the highest number of receptors could be detected in the semitendinosus autograft. The amount of free nerve endings was higher in the semitendinosus and patellar tendon autografts than in the control; the allografts showed the lowest number of receptors. With increasing time after reconstruction, the number of both types of receptors showed a decrease in the semitendinosus graft, whereas it increased in the patellar tendon graft and allograft. The number of mechanoreceptors in the semitendinosus and patellar tendon graft decreased over time after graft-failure, whereas it increased slightly in the allograft. Conclusion This study was the first to identify mechanoreceptors in human transplants of the anterior cruciate ligament. The partial increase in the number of receptors over time after reconstruction could indicate a reinnervation of the grafts.